2015
DOI: 10.1245/s10434-015-5022-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Indocyanine Green for Sentinel Lymph Node Mapping in Early Stage Endometrial and Cervical Cancer: Comparison with Conventional Radiotracer 99mTc and/or Blue Dye

Abstract: PurposeTo compare the detection rate (DR) and bilateral optimal mapping (OM) of sentinel lymph nodes (SLNs) in women with endometrial and cervical cancer using indocyanine green (ICG) versus the standard technetium-99m radiocolloid (99mTc) radiotracer plus methylene or isosulfan blue, or blue dye alone.MethodsFrom October 2010 to May 2015, 163 women with stage I endometrial or cervical cancer (118 endometrial and 45 cervical cancer) underwent SLN mapping with 99mTc with blue dye, blue dye alone, or ICG. DR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 27 publications
1
86
0
7
Order By: Relevance
“…Current data favor the use of ICG. 14,15 The entire procedure takes place in the operating room after anesthesia, sparing the patient any discomfort. Its optimal visibility identifies fluorescent LNs very clearly and helps locate SLNs in unusual places and over a broad area.…”
Section: Discussionmentioning
confidence: 99%
“…Current data favor the use of ICG. 14,15 The entire procedure takes place in the operating room after anesthesia, sparing the patient any discomfort. Its optimal visibility identifies fluorescent LNs very clearly and helps locate SLNs in unusual places and over a broad area.…”
Section: Discussionmentioning
confidence: 99%
“…26 As previously discussed, recent data on the role of sentinel lymph node (SLN) in the surgical staging of early EC staging are changing the paradigms of surgical management of this disease. 27 In addition, the introduction of the green indocyanine for the SLN mapping has significantly increased the detection rate of this technique, 28 and the availability of new imaging technology further increases the number of EC patients enrolled. To date, in most referral gynecological cancer centers, prospective trials on survival impact of SLN in early EC are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ICG dye is injected while the patient is under anesthesia, which avoids the painful administration of radiocolloid performed in the preoperative setting. Lastly, the cost of the ICG dye technique is significantly lower than with the combined technique because additional injection time and lymphoscintigraphy are not required [18]. Given the high rates of morbidity associated with complete lymphadenectomy in this setting and that ICG dye may represent a superior SLN detection technique compared to other mapping methods, further investigation of ICG and other fluorescent dyes is merited.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies in open surgery reported poor overall detection rates of just over 75% [11]. However, laparoscopic techniques with ICG have proven more successful in gynecologic cancer [14,15,1820]. Several studies evaluating ICG for SLN mapping in endometrial cancer also included cervical cancer cases in their publications [18,19].…”
Section: Discussionmentioning
confidence: 99%